Impact of Photosynthetic Efficiency on Watermelon Cultivation in the Face of Drought - Silva, Dayane Mércia Ribeiro; Barros, Allan Cunha; Silva, Ricardo Barros; Galdino, Wesley de Oliveira; Souza, José Wilker Germano de; Marques, Isabelly Cristina da Silva [UNESP]; Sousa, Jadielson Inácio de; Lira, Viviane da Silva; Melo, Alan Fontes; Abreu, Lucas da Silva de; Albuquerque Júnior, Elias de Oliveira; Barbosa, Luana do Nascimento Silva; et al. (MDPI, 2024)
Water availability is a limiting factor for plant production, especially in Brazilian semi-arid regions. The main aim of the study was to investigate the physiological effects of drought during the fruiting stage of watermelon cultivation. A completely randomized block design with four replications and six treatments varied by the number of lateral drip tapes (1 or 2) and the duration of drought stress (0, 4, and 8 days) was used. The following parameters were evaluated: relative chlorophyll content, relative leaf water content, electrolyte leakage, CO2 assimilation (A), stomatal conductance (gs), internal CO2 concentration, leaf temperature, transpiration (E), water use efficiency (WUE), carboxylation efficiency (CE), yield, thickness, diameter, length, and fruit °brix, at 4 and 8 days of drought. Drought negatively affected photosynthesis, particularly in treatments with a single dripper and 4 days of drought, resulting in reductions of up to 60% in A, 68% in gs, 44% in E, 58% in WUE, and 59% in CE, but did not have a significant effect on watermelon yield after 4 or 8 days of irrigation. It was concluded that drought influences the physiological responses of watermelon plants, mainly in reducing photosynthesis, but does not drastically affect fruit productivity in short periods of stress.
Keywords: Citrulus lanatusThumb. Mansf; photosynthesis; water deficiency; yield